of the University: from the Intersection of Europe to the Crossroads of the World - Motunova, Inna (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2019)
The article considers the history of the university through the prism of its international character, it explores the role of internationality in the history of the formation of this institution, what characteristics it had at different stages, how the national composition of the student body has changed and affected the functioning of the university. It is shown that the diversity of the ethnic composition of the student body played a significant role in shaping the organization structure and development of the university. The first universities were combined representatives of cultures belonging to one civilization. Now the universities will combine representatives of cultures of the different civilization identity, and mass of higher education deprives such countries as Ukraine the universal language of study.